2005
DOI: 10.1128/iai.73.11.7375-7380.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Immunization with a Malaria Transmission-Blocking Vaccine Candidate, Pfs25, Induces Complete Protective Immunity in Mice against Field Isolates of Plasmodium falciparum

Abstract: Malaria transmission-blocking vaccines based on antigens expressed in sexual stages of the parasites are considered one promising strategy for malaria control. To investigate the feasibility of developing noninvasive mucosal transmission-blocking vaccines against Plasmodium falciparum, intranasal immunization experiments with Pichia pastoris-expressed recombinant Pfs25 proteins were conducted. Mice intranasally immunized with the Pfs25 proteins in the presence of a potent mucosal adjuvant cholera toxin induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…in mice administered intranasally with crV without cT, both igG 1 and igG 2a levels were generally low, and more igG 1 seemed to be induced than igG 2a . however, intranasal immunization with crV/cT, in the presence of cT, induced mixed igG 2a /igG 1 . interestingly, all mice intranasally immunized with crV/cT showed high igG 2a levels, whereas enhancement of igG 1 production was only observed in some of them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…in mice administered intranasally with crV without cT, both igG 1 and igG 2a levels were generally low, and more igG 1 seemed to be induced than igG 2a . however, intranasal immunization with crV/cT, in the presence of cT, induced mixed igG 2a /igG 1 . interestingly, all mice intranasally immunized with crV/cT showed high igG 2a levels, whereas enhancement of igG 1 production was only observed in some of them.…”
Section: Resultsmentioning
confidence: 99%
“…horseradish peroxidase (hrP)-conjugated goat antimouse IgG (Gamma chain specific), HRP-conjugated goat anti-mouse igG 1 , and hrP-conjugated goat antimouse igG 2a were purchased (ZYmED, san Francisco, cA). hrP-conjugated goat anti-mouse igA (siGmA Aldrich japan, Tokyo, japan) was also used in this study.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the same authors confirmed that intranasal immunization with the P. falciparum homologue of Pvs25, Pfs25, also induced strong serum antibodies when co-administered with CT, and the antibodies could completely block parasite transmission to mosquitoes. 67 Intranasal immunization of mice with MSP1 19 , either from P. yoelii (PyMSP1 19 ) or P. vivax (PvMSP1 19 ), was also shown to induce serum antibodies and protect the immunized mice against parasite challenge in the case of PyMSP1 19 . 69,70 For delivery via the oral route, recombinant proteins are commonly encapsulated in particulate formulations to protect them against degradation and enhance their uptake by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Successful immunization via the intranasal route of recombinant protein in an effective mucosal adjuvant has been reported for Plasmodium antigens. [67][68][69][70] Recombinant P. vivax ookinete surface protein Pvs25 was shown to induce transmission-blocking serum antibodies when given intranasally to mice in the presence of cholera toxin (CT). 68 The level and isotype profile of the antibodies were comparable to those induced by intraperitoneal immunization with alum-adsorbed Pvs25.…”
Section: Discussionmentioning
confidence: 99%